The time-course of processing of grammatical class and semantic attributes of words: Dissociation by means of ERP - Yudes-Gómez, Carolina; Domínguez, Alberto; Cuetos, Fernando; de Vega, Manuel (Psicológica, 2017)
This study explores the time-course of word processing by grammatical class (verbs vs. nouns) and meaning (action vs. non-action) by means of an ERP experiment. The morphology of Spanish words allows for a noun (e.g., bail-e [a dance]) or a verb (e.g., bail-ar [to dance]) to be formed by simply changing the suffix attached to the root. This facility results in a set of nouns and verbs that are nearly matched in meaning, because of their shared root. The results show that grammatical class of words is processed very early, around 200 ms after the word onset, with the effects remaining activated at left frontal regions until 800 ms. Later components show a focal LAN sensitive to the noun-verb distinction, and a broadly distributed N400-like waveform sensitive to meaning. The different components affected by grammar (P200 and LAN) and meaning (N400) and their topographical dissimilarity seem to indicate an independent neural processing of these two linguistic properties and support a lexical specification of grammatical class.
Keywords: JCR